2013
DOI: 10.1590/s0080-623420130000500012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the disease: acceptability, ceiling and floor effects and reliability of an instrument on heart failure

Abstract: This study evaluated the acceptability, ceiling/floor effects, and the reliability of the instrument for measuring the Impact of the Disease on the Daily Life of Patients with Valvular Disease (IDCV) when applied to 135 patients with heart failure (HF). Acceptability was evaluated by the percentage of unanswered items and by the proportion of patients who responded to all items; the ceiling/floor effects by the percentage of patients who scored in the top of 10% best and worst results of the scale, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
4
19
0
1
Order By: Relevance
“…These results coincide with those obtained in previous studies 14 - 15 . In the study among patients with heart failure we observed an ICC> 0.96 for most IDCV fields except for the field Adaptation to the Disease 14 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results coincide with those obtained in previous studies 14 - 15 . In the study among patients with heart failure we observed an ICC> 0.96 for most IDCV fields except for the field Adaptation to the Disease 14 .…”
Section: Discussionsupporting
confidence: 92%
“…Although IDCV was originally developed for evaluation of beliefs from valvular disease patients, it appears that the set of statements that compose it assesses the impact of chronicity imposed by different cardiovascular diseases 11 . The instrument obtained satisfactory psychometric performance when applied in CAD ​​patients 12 - 13 , those with heart failure 14 , just as in hypertensive patients 15 . …”
Section: Methodsmentioning
confidence: 99%
“…A value of skewness greater than +1 indicates substantial floor effect while a value smaller than −1 indicates substantial ceiling effect (Chan & Pang, 2015). The proportion of participants obtaining the top 10% (i.e., total score >21) or bottom 10% (i.e., total score: <3) of the possible score range was also considered (Rodrigues Sde et al., 2013). The proportion of paticipants that is greater than 20% was considered as substantial ceiling or floor effects (Chan & Pang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The application of the IDCV to patients with CAD is justified by the evidence that the set of its items is relevant to measure the impact on patients with heart diseases with symptoms similar to that of valvular heart disease (10)(11)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%